![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
(17x-25):8+65=92
(17x-25):8 =92-65
(17x-25):8 =27
(17x-25) =\(27\times8\)
(17x-25) =216
17x =216+25
17x =241
x =241:7
x =\(\frac{241}{17}\)
T mk nhé bạn ^...^ ^_^
(17x-25):8+65=92
(17x-25):8=92-65
(17x-25):8=27
(17x-25)=27.8
17x-25=216
17x=216+25
17x=241
x=241:17
x=
![](https://rs.olm.vn/images/avt/0.png?1311)
a,-2x -(x-17)=34-(-x+25)
-2x-x+17=34+x-25
-3x+17=9+x
-3x-x=9-17
-4x=-8
-->4x=8
x=8:4
x=2
Vậy x=2
b,17-(16x-37)=2x+43
17-16x+37=2x+43
20-16x=2x+43
-16x-2x=43-20
-18x=23
x=23:(-18)
x=23/-18
Mà x là số nguyên nên --> x thuộc tập rỗng
c,-2x-3.(x-17)=34-2(-x+25)
-2x-3x+51=34-2.(-x)-25
-5x+51=9-(-2).x
-5x+(-2).x=9-51
-7x=-42
7x=42
x=42:7
x=6
Vậy x=6
![](https://rs.olm.vn/images/avt/0.png?1311)
17x + 4x = 86 : 86 + 20160
21x = 1+ 1
21x = 2
x = 2 : 21
x = \(\frac{2}{21}\)
TL : 17x\(\frac{2}{21}\)+ 4 x \(\frac{2}{21}\)= 86: 86 + (2016)0
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 6x - 35 + 5x - 21 = (6x + 5x) - (35 + 21) = 11x - 56 = 17x - 20 => 11x = 17x - 20 + 56 = 17x + 36
=> 36 = 11x - 17x = -6x => x = 36 : (-6) = -6
b) 5x + 35 - 4x - 27 = (5x - 4x) + (35 - 27) = x + 8 = 14x + 34 => x = 14x + 34 - 8 = 14x + 26
=> 26 = x - 14x = -13x => x = 26 : (-13) = -2
![](https://rs.olm.vn/images/avt/0.png?1311)
17x - 4x = 8^2 + 1
(17 - 4 )x = 64 + 1
13x = 65
x = 65 : 13
x = 5
![](https://rs.olm.vn/images/avt/0.png?1311)
17x - 4x = 88:86+(2016)0
<=> 82 + 1 = 13x
<=> 65 = 13x
<=> x = 5
\(17x-4x=8^8:8^6+\left(2016\right)^0\)
\(\Rightarrow13x=8^2+1\)
\(\Rightarrow13x=65\)
\(\Rightarrow x=5\)
Vậy \(x=5\)
\(17x-4x=65\)
\(\left(17-4\right)x=65\)
\(13x=65\)
\(x=65:13\)
\(x=5\)
Vậy x=5
Bài làm
17x - 4x = 65
( 17-4 )x = 65
13 x = 65
x = 65:13
x = 5
Vậy x = 5